2023
DOI: 10.1029/2022ef003230
|View full text |Cite
|
Sign up to set email alerts
|

The Pakistan Flood of August 2022: Causes and Implications

Abstract: The risk of floods has increased in South Asia due to high vulnerability and exposure. The August 2022 Pakistan flood shows a glimpse of the enormity and devastation that can further rise under the warming climate. The deluge caused by the floods in 2022, which badly hit the country’s southern provinces, is incomparable to any recent events in terms of the vast spatial and temporal scale. The flood event is ranked second in human mortality, while this was the top event that displaced about 33 million people in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(50 citation statements)
references
References 95 publications
(136 reference statements)
1
34
0
Order By: Relevance
“…4a), suggesting a self-amplification between convection and circulation. Recent study reported that the atmospheric river from the Arabian Sea was the dominant factor to lead to the record rainfall over Pakistan in August 19 .…”
Section: Tropical-extratropical Interactionmentioning
confidence: 99%
See 1 more Smart Citation
“…4a), suggesting a self-amplification between convection and circulation. Recent study reported that the atmospheric river from the Arabian Sea was the dominant factor to lead to the record rainfall over Pakistan in August 19 .…”
Section: Tropical-extratropical Interactionmentioning
confidence: 99%
“…A tropical storm occurred in the Arabian Sea in August but did not make landfall and therefore did not contribute to the observed excessive rainfall. That is, the excessive rainfall in August was primarily caused by the third monsoon surges 19 . A mid-to upper-level blocking high over northeastern Europe was observed (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…In August 2022, Pakistan experienced an exceptional flood caused by the multi-day anomalously high rainfall (Nanditha et al 2023). Pakistan received about twice (180%) of the long-term mean rainfall in July 2022 (Qamer et al 2023) that saturated the soil before the extreme precipitation event in August.…”
Section: Introductionmentioning
confidence: 99%
“…The devastating floods in 2010 and 2022 made notable occurrences, and both disasters dramatically altered how the community understood and responded to risk. In 1995, the flood resulted in the loss of 600 lives and displacement of 600 000 individuals (Nanditha et al 2023). Moving forward to 2010, the flood covered an extensive area of 160 000 km 2 , claiming 1985 lives and displaced approximately 20 356 550 people.…”
Section: Introductionmentioning
confidence: 99%
“…With land‐atmosphere interactions, under a relatively stable atmospheric boundary layer (e.g., atmospheric blocking) during a heatwave period, the increasing water vapor within the atmosphere may cause compound pluvial–hot extremes or may induce compound dry–hot extremes otherwise. Compound pluvial–hot events increase the likelihood of urban floods, landslides, mudslides, and crop failures (Gu et al., 2022; Liao et al., 2021; Nanditha et al., 2022), while compound dry–hot events aggravate the risk of tree mortality, public health burden, wildfire, air pollution, and agricultural losses (Deser et al., 2020; Gaupp et al., 2019; Raymond et al., 2020; Zscheischler et al., 2018). Thus, it is critical to identify hot spots of compound climate extremes in a changing climate for advancing climate change adaptation measures.…”
Section: Introductionmentioning
confidence: 99%